Per-Capita Medicare Expenditures, Primary Care Access, Mortality Rates, and the Least Healthy Cities in America - Weeks, Bill; Weinstein, James (The American Journal of Medicine, 2016)
Abstract Purpose To determine whether several measures of health care expenditures, access, and outcomes for the 25 recently identified "least healthy cities in America" differed from those in the rest of America. Methods For 2004 and 2013, we obtained publicly available price-, age-, sex-, and race-adjusted hospital service area per-capita Medicare expenditures; age-, sex-, and race-adjusted Medicare mortality rates; and 2 indicators of primary care access: the proportion of enrollees having at least one ambulatory visit to a primary care clinician and the per-capita discharge rate for ambulatory care sensitive conditions. Using population weighting, we used Student t test for expenditure data and the chi-squared test for access and outcomes data to compare results of the 25 least healthy cities in aggregate to the rest of America. Results In both years examined, the 25 least healthy cities had substantially (about 500 per capita per year) and statistically significantly higher total per-capita Medicare Part A and Part B expenditures than the rest of America: about 4/5 of this difference was due to higher hospital and skilled nursing facility expenditures; physician expenditures were modestly lower in the 25 least healthy cities. While a greater proportion of Medicare beneficiaries in the least healthy cities had a primary care clinician both years, mortality and ambulatory care sensitive condition admission rates were substantially higher in the least healthy cities. Conclusions Policymakers and health system executives should work together to determine the best asset allocation across determinants of health that maximizes value creation from a community health perspective.